Ta’wīl as Quranic Hermeneutics in the Philosophical Thought of Ibn ‘Arabī - Halim, Abdul (Islamic Studies Review, 2024)
Various methods for interpreting and understanding religious texts have long been developed in Islam. The development of this tradition is intricately linked to the need to interpret Islam's holy book, the Qur’an. It is widely understood that the verses of the Qur’an have various dimensions, namely the muhkâm (clear) and mutasyâbih (ambiguous), ‘âmm (general), khash (specific), qath’i (definitive), and dhanniy (presumptive). To address this, ta’wil was developed as method of textual interpretation. Ibn ‘Arabi represents a significant figure in the history of Islamic philosophical Sufism. He believed that for everything that appears literal, external, or exoteric (zhâhir), there is always a connection to something hidden, spiritual, internal, or esoteric (bâthin). For Ibn ‘Arabi, ta’wil is an esoteric spiritual interpretation that understands all material data and facts as symbols to transmute and “return” them to what is being symbolized. Every manifestation, every exoteric meaning (zhâhir), always has an esoteric meaning (bâthin). In other words, ta’wil is a process of interpretation that involves delving into the furthest depths of symbols to uncover the spiritual secrets of the text. The creative imagination of the interpreter plays a significant role in the process of ta’wil, serving as a mediator between the hidden divine essence and the manifestation of the pluralities of nature, akin to the world of ideas, culminating in the concept of symbols. Symbols are reflections of exemplars (mitsâl) of the sensory world depicted within the hierarchy of presence (hadhrâh), namely the presence of essence (hadhrah al-dzât), the Divine presence (hadhrah al-ulûhiyyah), the presence of various Divine actions or deeds (hadhrah al-af’âl, hadhrah rubûbiyyah), the presence of shadows and active imagination (hadhrah al-mitsâl wa al-khayyâl), and the sensory and visible presence (hadhrah al-hiss wa al-musyâhadah). In this context, the creative imagination of the interpreter, generated through the ascent to a higher meaning, is a new creation that recurs (khalq jadîd), a divine manifestation (theophany), with the heart as the Divine Presence within the interpreter. For this reason, ta’wil (as a method of text interpretation) necessitates extensive knowledge, comprehension, a willingness to engage with the text’s substance, adherence to legitimate and authoritative sources, and an interpreter’s inventiveness. Ta’wil, therefore, represents a blend of empirical, rational, and intuitive methods, emphasizing the spiritual perspective of reason to achieve the truth.